Ultimate bearing capacity of saturated reinforced horizontal ground. Issue 1 (16th September 2015) - Huang, C.-C.
Abstract : The effects of soil saturation on the ultimate bearing capacity characteristics of reinforced and unreinforced horizontal sandy ground were investigated using a 100-mm-wide rigid strip footing. The test results revealed that saturation of the soil influenced the ultimate bearing capacity characteristics of unreinforced and reinforced ground in two ways: a reduced effective self-weight of the soil and an apparent cohesion induced by negative excess pore pressures. Ground saturation had a major influence on the footing settlement at peak footing load ( S p ) partially due to the existence of negative excess pore water pressures. Values of S p for the saturated ground were 100–200% larger than those for the dry one, regardless of the reinforcement state. For both saturated and dry reinforced ground, the moment of peak footing load was consistent with that of the maximum reinforcement force, revealing the effectiveness of geosynthetic reinforcement for enhancing the ultimate bearing capacity of the footing. An equation extended from that proposed in an earlier publication by the author and a colleague was used to simulate the effects of reinforcement and apparent cohesion of the saturated ground. The calculated values of bearing capacity ratio agreed well with the measured values.